Vulneración del principio de igualdad tributaria respecto a la prescripción de la acción de cobro frente a los plazos otorgados para la prescripción por pago indebido o del pago en exceso - Jiménez Jiménez, Silvia katerine (2018)
The Ecuadorian tax system is regulated by the Tax Code in which rights and guarantees are recognized to the subjects of the tax obligation by the State as an active subject and the taxpayer as a taxpayer. The prescription is a figure of tax law, which, when configured, entails the extinction of rights and obligations due to the inaction of the creditor and lack of recognition of the debtor among themselves, but when speaking of different terms for this figure to be configured, such is the case that establishes 5 and 7 to prescribe the action of collection of tax credits by the administration and the period of 3 years for the claim action that the taxpayer may present for undue payment or excess payment, evidencing a problem that affects the taxpayer and that goes against constitutional principles such as equality and equity. This discriminatory situation that contradicts constitutional principles affects patrimonial interests and the fundamental rights of taxpayers, for which reason it is the object of study in this work that is entitled: "VULNERATION OF THE PRINCIPLE OF TAX EQUALITY WITH RESPECT TO THE PRESCRIPTION OF THE ACTION OF COLLECTION FRONT AT THE PERIODS GRANTED FOR THE PRESCRIPTION FOR MISAPPROVED PAYMENT OR EXCESS PAYMENT ", the research is based on a theoretical basis in response to the objectives in which doctrinal and legal conceptual opinions are presented, this in response to the objectives set out in the project . 5 The methodology applied has allowed us to demonstrate through the investigation and analysis of how it affects the establishment of different terms so that the prescription is configured in the tax system and the discriminatory treatment established with the mentioned terms. Through the survey and interview it was possible to obtain the criterion of citizenship and the unequal treatment established with the terms for the prescription was concluded, and the advantage created in favor of the State. In terms of results obtained based on the field research process, all of which allows us to conclude that there is a need to reform the Tax Code with respect to the deadlines for the prescription to be set and that the rights of taxpayers be effectively guaranteed, on the basis of constitutional principles and the tax system and with this reform seek to assimilate the deadlines and ensure fair and equitable. It is necessary to extend the term from three to five years, so that the taxpayer can exercise his right to formulate the claim or the action of undue payment or payment in excess, in order to eliminate the advantage with which the administration has for the collection of tax debts that is 7 years, an advantage that translates into a violation of the principle of equality, by creating advantages or unjustifiable differences.